Understanding the relations between parents of children with autism spectrum disorder and treatment staff in the context of Singapore's social policy and social atttitudes. - Seah, ShiMin. (2013)
This paper examines how parents of children with Autism Spectrum Disorder (ASD) and the treatment staff negotiate a relationship—the nature of the tensions, their causes and the means by which they are resolved. Findings suggest that the Singapore state’s emphasis on personal responsibility coupled with the lack of funding and of quality and affordable public healthcare services, burdens parents and contributes to already tensed encounters within the clinical setting. This paper encourages a rethinking of the parent-professional relationship as influenced not only by micro-level processes, as the homogeneity of experiences reflects larger issues in the social structure. Ultimately, the paper informs us of possible implications of the state’s policy and suggests that more needs to be done in terms of providing facilities and affordable services as well as changing the social attitudes to further improve parents’ quality of life and consequently promote better outcomes for the child.